(untitled) (International Journal of Physiotherapy, 2020)
Background: Today, anterior cruciate ligament rupture is the most common injury in sportsmen and women, but it can also occur in sedentary subjects. Its treatment, always adapted to the patient’s lifestyle, age, and will, often remains surgical. However, despite its frequency and universality, we still find gait disorders after the surgery and can up to several months or even several years after the surgery. Therefore, the present study is interested in determining the risk factors associated with gait disorders after an anterior cruciate ligament reconstruction (ACLR). This study aims to determine the risk factors associated with gait disorders after surgery with hamstring autograft. We are interested in the factors that may exist at 3 and 6 months postoperatively. Methods: Two populations participate in this study, a healthy population and a population with ACLR subjects. The ACLR test group is divided into two subgroups, one with a post-operative delay of 3 months and the second with a delay of 6 months. All subjects are subjected to the same protocol; their gait on the treadmill was analyzed and evaluated by the device OptoGait®. A united and varied analysis was first conducted, and then a multivariate analysis by adjustment method was carried out to eliminate potential confounding factors. Results: Comparison of the results across populations in the unvaried analysis shows an absence of significant results (p>0,05); however, there are trends. The statistical results of the multivariate analysis showed interactions in the two subgroups of the ACLR population. At three months after surgery, there is a tendency for gait disorders to worsen in subjects with a BMI reflecting overweight, when an associated surgical procedure on the meniscus was realized, in subjects over 35 years old and in males subjects. In contrast, at six months after surgery, the worsening trend is only seen in the subgroups represented by subjects with BMI reflecting overweight subjects with meniscal repair associated with ACLR. Conclusion: The present study results show certain factors tend to aggravate these gait disorders after ACLR with hamstring autograft; these factors are different depending on the post-operative delay.